Development of Android-Based Learning Media (Thunkable) on Work and Energy Materials for Class VIII Junior High Sechool - Nikmah, Rodhotun; Firdaus, Thoha; Sinensis, Arini Rosa (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to produce android-based (thunkable) physics learning media on work and energy materil as a form of utilizing tecnology to assist educators in delivering learning material. With this android-based (thunkable) learning media, students can learn while at school or while studying at home. The research method used in this research is Research and Development (R&D) using a 4D approach including Define, Design, Develop, and Disseminate, based on validation carried out by 3 media experts and 3 material experts, each of which had an average score of 84.2% (by media experts) and an average score of 81% (by material experts), it can be councluded that android-based learning media (tunkable) is feasible and very practical for users to use. In this android-based (thunkable) learning media product, researchers developed and applocation that contains objectives, material and examples questions, videos, simulation and also learning evaluations to make it easier for users to understand the material presented.